Estudo sobre preferência de cores para forrageamento de borboletas em cativeiro no borboletário municipal de Osasco/SP, Brasil - Maciel, Julia Maria Pais (Universidade Federal de São Carlos, 2020)
Lepidoptera are holometabolic, charismatic, colorful and easily sampled animals. They are divided between butterflies and moths. The feeding type are divided between those who eat nectar or those who eat fruit. Some species are generalists and can feed on both. Nectarivorous lepidopterans show preference in the foraging of some flowers due to their color and smell. The feeding preference of Heliconius erato (nymphalidae), Phoebis neocypris (Pieridae) and Siproeta stelenes (nymphalidae) was observed at the Borboletário Municipal de Osasco/ SP, where it was noted that, both for H. erato has preferences for yellow and Orange over blue and green and na olfactary preference in the floral scent of Lantana Camara. Already P. neocypris had their landings in red color noting similarity with nature, since they feed on flowers with vibrant colors and also Lantana câmara, but that generalista species like S. stelenes have no preference for any color, because they act concomitantly as a kind of nectarivorous and frugivorous habits. The captivity presents an effective environmental enrichment, with species of flowers that fit the psychophilia syndrome, in addition to Lantana Câmara, Heliconius' favorite flower.
Study on color preference for foraging butterflies in captivity in the "municipal borboletário de Osasco"/SP, Brazil
Keywords: Lepidópteros; Forrageamento; Cativeiro; Enriquecimento ambiental; CIENCIAS BIOLOGICAS::ECOLOGIA